2005
DOI: 10.1016/j.neuron.2005.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Farnesylation of Retinal Transducin Underlies Its Translocation during Light Adaptation

Abstract: G proteins are posttranslationally modified by isoprenylation: either farnesylation or geranylgeranylation. The gamma subunit of retinal transducin (Talpha/Tbetagamma) is selectively farnesylated, and the farnesylation is required for light signaling mediated by transducin in rod cells. However, whether and how this selective isoprenylation regulates cellular functions remain poorly understood. Here we report that knockin mice expressing geranylgeranylated Tgamma showed normal rod responses to dim flashes unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 50 publications
(80 reference statements)
3
44
1
Order By: Relevance
“…Great progress has been made in the past few years by using mouse (or rat) models for study. Both Gα t1 and Gβ 1 γ 1 subunits are present predominantly in the ROS in darkness, but translocate in bright light, with slightly different time courses, to the inner segment and the inner nuclear layer [72,73]. This phenomenon has been suggested to contribute to light adaptation of rods [72], but others argue that the main function of transducin translocation is to provide protection for rods in bright light when rods contribute little to vision [74].…”
Section: Transducinmentioning
confidence: 99%
See 1 more Smart Citation
“…Great progress has been made in the past few years by using mouse (or rat) models for study. Both Gα t1 and Gβ 1 γ 1 subunits are present predominantly in the ROS in darkness, but translocate in bright light, with slightly different time courses, to the inner segment and the inner nuclear layer [72,73]. This phenomenon has been suggested to contribute to light adaptation of rods [72], but others argue that the main function of transducin translocation is to provide protection for rods in bright light when rods contribute little to vision [74].…”
Section: Transducinmentioning
confidence: 99%
“…What is the significance of this difference? Knock-in mice expressing geranylgeranylated instead of farnesylated Gγ 1 exhibited impaired properties in light adaptation because the stronger attachment by geranylgeranylation attenuated the light-dependent translocation of Gγ 1 from ROS to the inner region [73]. Thus, it appears that the selective farnesylation is important for the regulation of visual sensitivity by providing sufficient but not excessive anchoring of Gβ 1 γ 1 to the membrane.…”
Section: Transducinmentioning
confidence: 99%
“…Finally, transducin subunits escape from the outer segment separately from one another, as evident from the difference in their translocation kinetics (Sokolov et al, 2002;Kassai et al, 2005;Calvert et al, 2006). Most likely, they diffuse through the rod cytoplasm (Sokolov et al, 2004;Nair et al, 2005), although a few studies suggest the involvement of molecular motors (McGinnis et al, 2002;Peterson et al, 2005).…”
Section: Transducin Translocation Takes Place In Three Major Stepsmentioning
confidence: 99%
“…The ability of transducin subunits to dissociate from the disc membranes is expected to be determined primarily by the nature of their lipid modifications. Indeed, Kassai et al (2005) found that substitution of the farnesyl residue in G␥ 1 with a more lipophilic geranylgeranyl moiety impairs G␤ 1 ␥ 1 translocation despite a normal translocation of G␣ t .…”
Section: Transducin Translocation Takes Place In Three Major Stepsmentioning
confidence: 99%
“…Most G-protein ␥-subunits (G␥s) are modified with a thioether-linked isoprenoid geranylgeranyl (C20) attached to Cys residues within the C-terminal "CAAX" box (Escriba et al, 2006). In contrast, the rod-specific G␥ 1 carries the farnesyl moiety (C15), which facilitates light-dependent translocation of G t from the rod outer segment (ROS) to the inner compartments, thereby contributing to light adaptation (Kassai et al, 2005). G␣-subunits are typically modified with an amidelinked fatty acid myristate (C14:0) at the extreme N-terminal Gly residue and/or with a thioester-linked palmitate (C16:0) at Cys residues near the N termini (Wedegaertner et al, 1995;Chen and Manning, 2001).…”
Section: Introductionmentioning
confidence: 99%